The More Anxious, the More Dependent? The Impact of Math Anxiety on AI‐Assisted Problem‐Solving - Chen, Feng; Chen, Jihe; Xu, Yanying (Psychology in the schools, 2025)
ABSTRACT Although the use of AI technology driven by anxiety has become increasingly common, research on the relationship between high school students' math anxiety and their intention to use AI for problem‐solving remains limited. This study, grounded in the Stimulus‐Organism‐Response (SOR) model, aims to explore the relationship between math anxiety and the intention to use AI for solving math problems among high school students. Using the Math Anxiety Scale (AMAS), the Perceived Social Support Scale (PSSS), and the AI Problem‐Solving Behavior Scale (AIPS), data from 391 high school students were collected. The analysis revealed the following: (1) Students report high levels of math anxiety and a strong inclination to use AI tools for solving math problems; (2) Social support plays a significant role in alleviating math anxiety, with family support being the most effective, followed by support from friends and teachers; (3) High levels of family support are the most effective means of reducing math anxiety. The study suggests that the relationship between math anxiety and AI use intention should be addressed, with a focus on regulating the application of AI in math education to promote its scientific and effective use. Additionally, improving family relationships and providing mental health support are recommended to alleviate math anxiety from an emotional and social support perspective. This study provides valuable insights for educators and policymakers, offering important references for designing more human‐centered and effective educational interventions, thereby promoting the application of artificial intelligence technology in mathematics education. Practitioner Points High school students are inclined to use AI tools to solve math problems. Math anxiety leads to a stronger willingness to adopt AI tools. In the context of AI education, strengthening family support helps alleviate math anxiety.